Diazanorbornene: A Valuable Synthon towards Carbocycles and Heterocycles. Issue 42 (29th October 2020) - Preethalayam, Preethanuj; Jijy, E.; Prakash, Praveen; Chand Sarngadharan, Sarath; Vijayan, Ajesh; Radhakrishnan, K. V.; John, Jubi
Abstract : Desymmetrization of meso compounds is well recognized as a powerful method for delivering biologically relevant molecular skeletons in a few synthetic steps. Heterobicyclic olefins are a class of meso compounds which exhibit exceptional reactivity due to their high ring strain originating from the unfavorable bond angles and eclipsing interactions. Extensive research was carried out towards the synthetic transformations of oxa‐, aza‐, and diazanorbornenes/norbornadienes for the synthesis of a wide variety of carbocycles and heterocycles in a single step, most importantly in a stereo‐ and chemo‐selective manner. This review summarizes the relevant aspects of diazanorbornene reactivity which will inspire the synthetic community for exploiting these highly strained bicyclic systems for the creation of extensive libraries of novel structurally and biologically interesting molecules. The review is divided into several sections based on the type of reactions that diazanorbornenes are subjected to. Abstract : The present review summarizes the recent progress on desymmetrization of diazanorbornenes towards substituted/fused cyclopentanoids through catalyzed or uncatalyzed pathways.